Herbal Toothpaste Extracts (Betel Leaf, Lime, and Salt) to Reduce Plaque - Ajum Trinawati; Suwarsono Suwarsono; Salikun Salikun (Journal Center of Excellent : Health Assistive Technology, 2023)
Data from the 2018 Riskesdas reported that 96.5% of the 10-14 years old group had good tooth brushing behavior, namely brushing their teeth every day. However, from this percentage, only 2.1% brushed their teeth at the right time. Plaque cannot be removed be simply rinsing and sprying water. Plaque can only be completely removed by mechanical means. Herbal toothpaste is toothpaste that contains natural ingredients such as extracts (betel leaf, lime and salt). The addition of herbs to toothpaste is expected to inhibit plaque growth. The aim of the study was to determine the effect of herbal toothpaste with betel leaf extract, lime juice and salt to reduce plaque in grade IV children at Pudak Payung 01 Elementary School.The type of research used was descriptive quantitative with a cross-sectional approach. Namely by examining the plaque directly into the oral cavity of children who are research respondents. The results showed that the herbal extract paste (betel leaf, lime, and salt) was more effective and most significant in reducing the dental plaque score, which decreased by 22.2 with an average decrease in score of 1.2. It is hoped that children at Pudak Payung 01 Elementary School can always maintain healthy teeth and mouth by using herbal extract tooth paste (betel leaf, lime and salt).